I need help on this problem.. i think its suppose to be simple but i don't know how to get the answer.

the problem is:

solve the initial-value problem 2t^2y''+3ty'-y=0; y(1)=2,y'(1)=1

the answer is y(t)=2(t^1/2)

thank you

Results 1 to 6 of 6

- Jul 5th 2009, 12:08 AM #1

- Joined
- Jun 2009
- Posts
- 8

- Jul 5th 2009, 12:40 AM #2

- Joined
- May 2008
- Posts
- 2,295
- Thanks
- 7

- Jul 5th 2009, 12:45 AM #3

- Jul 5th 2009, 01:28 AM #4

- Jul 5th 2009, 11:36 AM #5

- Joined
- Jun 2009
- Posts
- 8

- Jul 5th 2009, 12:09 PM #6